Adoption of production technologies by potato growers in northwest Bangladesh - Uddin, A. B. M. Sharif; Rahman, M. M.; Alam, M. B.; Kamaly, M. H. K. (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
Determining the extent of adoption of modern variety potato production technologies by the potato growers was the main focus of the study. The study was conducted in the Rajshahi district. Out of 1547 potato growers, 232 respondents were randomly selected as a sample for data collection from twenty villages. A pre-tested interview schedule was used to collect data from the respondents during July 2010 to February 2011. For measuring the adoption of modern variety potato production technologies by the potato growers, 11 technologies on modern potato production were considered. Majority (46.55%) of the growers had medium adoption compared to high (29.74%) and low (23.71%) adoption. Among the extent of adoption of eleven selected technologies recommended irrigation was at top highest ranking as indicated by the adoption index where as plant spacing was bottom lowest. The adoption variations in different technologies will not be improved unless effective steps are taken to increase growers exposure to get benefits of using such technologies as per recommendations.